Analisis Pengelolaan Keuangan Objek Wisata Hutan Pinus Buntudatu Kecamatan Mengkendek Kabupaten Tana Toraja - Zhuhaeny Zhuhaeny; Adriana Madia Marampa; Stefani Marina Palimbong (Universitas Kristen Indonesia Toraja, 2023)
This study aims to analyze how the form of financial management is implemented in the Buntudatu Pine Forest Tourism Object. The type of research used is qualitative research with a descriptive approach. With data collection methods, namely interviews, documentation, and observation. The results of the research obtained are that financial management at the Buntudatu Pine Forest Tourism Object has been implemented but has not been maximized where planning has been carried out by the tourism object manager by holding village meetings in order to minimize expenses in order to get profits. The recording system is carried out every day manually using books or paper to record all income and expenditure transactions. And financial reporting has not been implemented because the knowledge possessed is still minimal, but the manager has made a year-end accountability report. Meanwhile, control has been carried out by holding evaluation meetings every month, to achieve a certain goal.